Intellectual property challenges in the crowdsourced software engineering: An analysis of crowdsourcing platforms - Al-bloush H.; Solemon B. (Springer Science and Business Media Deutschland GmbH, 2023)
Intellectual property; Software engineering; Academic research; Crowdsourcing platforms; Legal documents; Online platforms; Open collaborative environments; Ownership rights; Ownership statements; Crowdsourcing